CONSTRUCTION OF THREE-DIMENSIONAL MODEL OF PLATONIC SOLIDS UTILIZING METATRON’S CUBE - Isidora MITROVIC; Sonja KRASIC; Jovana TOMIC; Nastasija KOCIC (Journal of Industrial Design and Engineering Graphics, 2024)
The concept of Metatron's Cube, which is rooted in Sacred Geometry for centuries, is believed to contain the projections of all Platonic Solids. While Metatron's Cube inherently manifests as a two dimensional geometric form, this study incorporates its three-dimensional counterpart delving into the relationship between this sacred symbol and the Platonic Solids. The primary objective is to ascertain the viability of constructing the five Platonic Solids exclusively through their Metatron's Cube projections by experimenting in the fields of descriptive geometry and geometry in general. The experimentation strategically emphasizes simplicity and feasibility, seeking to unveil potential methodologies for constructing these Platonic Solids via the projections engendered by Metatron's Cube. Through the establishment of a connection between theoretical frameworks and practical applications, the study aims to contribute valuable insights into alternative and probably easier and more accessible methods of constructing Platonic Solids, particularly within the context of architectural design. This research represents a valuable stride in enhancing our understanding of ancient geometric concepts and their potential applications in contemporary architectural practices.